Separation and recovery of carbon powder in anodes from spent lithium-ion batteries to synthesize graphene - Li Yang (Nature Portfolio, 2019)
Abstract Based on the structural characteristics of the anodes of lithium-ion batteries, an improved Hummers’ method is proposed to recycle the anode materials of spent lithium-ion batteries into graphene. In order to effectively separate the active material from the copper foil, water was selected as an ultrasonic solvent in this experiment. In order to further verify whether lithium ions exist in the active material, carbon powder, it was digested by microwave digestion. ICP-AES was then used to analyse the solution. It was found that lithium ions were almost non-existent in the carbon powder. In order to further increase the added value of the active material, graphene oxide was obtained by an improved Hummers’ method using the carbon powder. The graphene material was also reduced by adding vitamin C as a reducing agent through a chemical reduction method using graphene oxide. Meanwhile, the negative graphite, graphite oxide and graphene samples were characterized by XRD, SEM, FTIR and TEM. The conductivity of the negative graphite, graphite oxide and graphene was tested. The results show that graphene prepared by a redox method has a better layered structure, less impurities and oxygen groups in its molecular structure, wider interlayer spacing and smaller resistivity.